Codon Usage and Adenovirus Fitness: Implications for Vaccine Development - Giménez-Roig, Judit; Núñez-Manchón, Estela; Alemany, Ramon; Villanueva, Eneko; Fillat, Cristina (Frontiers in Microbiology, 2021)
Vaccination is the most effective method to date to prevent viral diseases. It intends to mimic a naturally-occurring infection while avoiding the disease, exposing our bodies to viral antigens to trigger an immune response that will protect us from future infections. Among different strategies for vaccine development, recombinant vaccines are one of the most efficient ones. Recombinant vaccines use safe viral vectors as vehicles and incorporate a transgenic antigen of the pathogen against which we intend to generate an immune response. These vaccines can be based on replication-deficient viruses or replication-competent viruses. While the most effective strategy involves replication-competent viruses, they must be attenuated to prevent any health hazard while guaranteeing a strong humoral and cellular immune response. Several attenuation strategies for adenoviral-based vaccine development have been contemplated over time. In this paper, we will review them and discuss novel approaches based on the principle that protein synthesis from individual genes can be modulated by codon usage bias manipulation. We will summarize vaccine approaches that consider recoding of viral proteins to produce adenoviral attenuation and recoding of the transgene antigens for both viral attenuation and efficient viral epitope expression.